2018
DOI: 10.1093/carcin/bgy046
|View full text |Cite
|
Sign up to set email alerts
|

AFF4 promotes tumorigenesis and tumor-initiation capacity of head and neck squamous cell carcinoma cells by regulating SOX2

Abstract: AFF4, an essential core of SEC, was overexpressed in HNSCC tissue and cell lines. AFF4 promoted the proliferation, migration, invasion and tumor-initiation capacity by regulating SOX2 in HNSCC cells, indicating AFF4 may serve as a potential therapeutic target of HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…41 In head and neck squamous cell carcinoma cells, AFF4 can improve tumour initiation and tumorigenesis capability though SOX2. 42 Previous research found that Aff4/Af5q31-null mice exhibited azoospermia, suggesting a nonnegligible effect on Sertoli cells. Moreover, in regard to FRAXE, AFF4 remains functionally redundant during brain development.…”
Section: Discussionmentioning
confidence: 99%
“…41 In head and neck squamous cell carcinoma cells, AFF4 can improve tumour initiation and tumorigenesis capability though SOX2. 42 Previous research found that Aff4/Af5q31-null mice exhibited azoospermia, suggesting a nonnegligible effect on Sertoli cells. Moreover, in regard to FRAXE, AFF4 remains functionally redundant during brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed that altered overexpression of SOX2 is associated with cell proliferation, self-renewal, cancer cells plasticity, anti-apoptosis, tumorigenesis, tumor relapse and chemo-radio resistant leading to bad prognosis in TSCC patients [100] , [101] , [102] , [103] . Interestingly, specific silencing of SOX2 in TSCC significantly inhibits self-renewal and invasion capacities, in-vivo tumorigenicity and increases chemo-radio sensitization [104] .…”
Section: Various Molecular Approaches/signaling Pathways For Targetinmentioning
confidence: 99%
“…As an essential component of SEC, AFF4 can bind to DNA directly and regulate the transcription elongation of many genes. MYC and SOX2, well-known pluripotency factors of CSCs, have been reported to be regulated by AFF4 in BCa [11] and HNSCC [30], respectively. To investigate whether MYC and SOX2 are effectors of AFF4 in regulating the self-renewal capability of BCSCs, we performed CHIP assay in 5637 and UM-UC-3 cells and found AFF4 directly bound to MYC and SOX2 promoter regions, which were barely detectable after AFF4 knockdown ( Figure 5(a)).…”
Section: Aff4 Directly Regulates Myc and Sox2 Gene Expression In Bca mentioning
confidence: 99%
“…As a core component of the super elongation complex (SEC), AFF4 is involved in the regulation of transcription elongation of many genes encoding the pluripotency factors [ 28 , 29 ]. For instance, AFF4 could upregulate SOX2 transcription to promote the tumor-initiation capacity of head and neck squamous cell carcinoma (HNSCC) [ 30 ], and MYC is another known target of AFF4 [ 11 , 31 ]. Inspired by these results, we hypothesized that m 6 A plays a role in promoting the stemness of BCa cells by regulating AFF expression.…”
Section: Introductionmentioning
confidence: 99%